Characterization of a Novel Hypotrich Ciliate From Heavy Metal-Contaminated Industrial Outlet in Onsan, Ulsan, South Korea - Kumar, Santosh; Bharti, Daizy; Shazib, Shahed Uddin Ahmed; Shin, Mann Kyoon (Frontiers in Microbiology, 2021)
Very few studies exist on the description of protozoan ciliates from industrial contaminated sites. In this study, we report description of a novel hypotrich ciliate isolated from water samples collected from an industrially contaminated outlet in Onsan, Ulsan, South Korea. The oxytrichid ciliate, Histriculus tolerans n. sp., was investigated using live observation and protargol impregnation. The morphology, morphogenesis, and molecular phylogeny inferred from small-subunit (SSU) rRNA gene sequences were studied. The new species is mainly characterized by a cell size of about 70 × 40 µm in vivo, two elongate ellipsoidal macronuclear nodules and one or two micronuclei, adoral zone about 51% of body length with 32 membranelles on average, about 34 cirri in right and 24 cirri in left marginal row, 18 frontoventral transverse cirri, six dorsal kineties including two dorsomarginal rows, dorsal kinety 1 with 26 bristles.. Morphogenesis is similar to that of the type species, i.e., Histriculus histrio, except that oral primordium does not contribute to anlage II of the proter. Phylogenetic analyses, based on small-subunit rRNA gene sequences, consistently place the new species within the family Oxytrichidae clustering with Histriculus histrio.